2017
DOI: 10.3390/nu9030262
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Broccoli Alters Rat Cecal Microbiota to Improve Glucoraphanin Hydrolysis to Bioactive Isothiocyanates

Abstract: Broccoli consumption brings many health benefits, including reducing the risk of cancer and inflammatory diseases. The objectives of this study were to identify global alterations in the cecal microbiota composition using 16S rRNA sequencing analysis and glucoraphanin (GRP) hydrolysis to isothiocyanates ex vivo by the cecal microbiota, following different broccoli diets. Rats were randomized to consume AIN93G (control) or different broccoli diets; AIN93G plus cooked broccoli, a GRP-rich powder, raw broccoli, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 38 publications
6
68
2
Order By: Relevance
“…Operational taxonomic unit (OTU) picking was performed against SILVA ribosomal RNA database (132 release; Quast et al, 2013;Chen et al, 2018). Data interpretation, statistical analysis, and visualization were performed in MicrobiomeAnalyst (Dhariwal et al, 2017), including rarefaction to the minimum library size without scaling of data (Liu et al, 2017;Kaczmarek et al, 2019). Calculation of the alpha diversity scores, abundance-based Bray-Curtis dissimilarity (beta diversity), ordination via Non-Metric Multidimensional Scaling (NMDS), and linear discriminant analysis effect size (LEfSe) analysis (Segata et al, 2011) were each preformed using MicrobiomeAnalyst (Dhariwal et al, 2017).…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Operational taxonomic unit (OTU) picking was performed against SILVA ribosomal RNA database (132 release; Quast et al, 2013;Chen et al, 2018). Data interpretation, statistical analysis, and visualization were performed in MicrobiomeAnalyst (Dhariwal et al, 2017), including rarefaction to the minimum library size without scaling of data (Liu et al, 2017;Kaczmarek et al, 2019). Calculation of the alpha diversity scores, abundance-based Bray-Curtis dissimilarity (beta diversity), ordination via Non-Metric Multidimensional Scaling (NMDS), and linear discriminant analysis effect size (LEfSe) analysis (Segata et al, 2011) were each preformed using MicrobiomeAnalyst (Dhariwal et al, 2017).…”
Section: Data Analysesmentioning
confidence: 99%
“…Kruskal-Wallis tests were performed (Liu et al, 2017) comparing the alpha diversity scores between samples from Quebec and Nova Scotia. Multiple t-tests were performed comparing the abundance of each taxa in samples harvested from two sites in 2015/2018 (Graphpad Prism 8.2.1).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This however, would be dependent on the concentrations of ITCs in the human gut and as yet this question has not been fully addressed . A recent study has shown that the microbial conversion of GSLs to ITCs can be modified by the frequency of GSL consumption in rats and resulted in a change of the microbiota composition which is effectively an enrichment process for GSL‐utilizing bacteria. While some bacteria produce ITCs it is highly likely that other bacteria in the human gut will have the potential to detoxify these compounds so the situation with the microbiota is likely to be complex.…”
Section: Introductionmentioning
confidence: 99%
“…The main ingredient of hot-processed ginger is Shogaols, which has proven to be a very effective anti-cancer agent, and studies have shown that the coupled metabolite of Shogaols and cysteine can be used as a novel dietary preventive agent for colon cancer [141]. Liu et al have evidence that the main triggers of colon cancer are infl ammation and intestinal fl ora, and regular consumption of broccoli not only has great benefi ts for our health, but also reduces the risk of cancer and infl ammatory diseases, thereby preventing colon cancer [142]. Del Pino-García et al have found that red wine pomace seasoning has anti-proliferative and antigenic toxic effects, and has the potential to prevent colon cancer [143].…”
Section: Preventionmentioning
confidence: 99%